2019
DOI: 10.1096/fj.201901247r
|View full text |Cite
|
Sign up to set email alerts
|

Dazl determines primordial follicle formation through the translational regulation of Tex14

Abstract: Deleted in azoospermia-like (DAZL) is a germ cell RNA-binding protein that is essential for entry and progression through meiosis. The phenotype of the Dazl knockout mouse has extensive germ cell loss because of incomplete meiosis. We have created a Dazl hypomorph model using short interfering RNA knockdown in mouse fetal ovary cultures, allowing investigation of Dazl function in germ cell maturation. Dazl hypomorph ovaries had a phenotype of impaired germ cell nest breakdown with a 66% reduction in total foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…5, B and C ). Considering the role of Dazl in licensing for meiosis ( 20 ) and its function in translational regulation of TEX14 in cultured mouse embryonic ovaries ( 21 ), we compared Dazl expression and confirmed that levels were comparable between Tex14 +/− and Tex14 −/− (fig. S5A).…”
Section: Resultsmentioning
confidence: 72%
“…5, B and C ). Considering the role of Dazl in licensing for meiosis ( 20 ) and its function in translational regulation of TEX14 in cultured mouse embryonic ovaries ( 21 ), we compared Dazl expression and confirmed that levels were comparable between Tex14 +/− and Tex14 −/− (fig. S5A).…”
Section: Resultsmentioning
confidence: 72%
“…Our study examines the earliest stages of gonadogenesis and provides evidence that the conserved RBP, Dazl, is required for germline cyst formation and plays critical roles in germ cell amplification, and acts upstream of meiosis and establishment of germline stem cells to promote fertility. Immunoaffinity screens for Dazl targets have identified regulators of incomplete cytokinesis (Kim et al, 2015;Reynolds et al, 2005;Rosario et al, 2019;Rosario et al, 2017;Zagore et al, 2018). This work provides genetic evidence that Dazl is required to form germline cysts interconnected by ring canals.…”
Section: Discussionmentioning
confidence: 79%
“…Although Dazl has not been shown to be required for cyst formation, we reasoned that Dazl was a compelling candidate regulator of this conserved process, since in mouse and human fetal ovary it interacts with Tex14, a regulator of ring canal formation (Greenbaum et al, 2006;Reynolds et al, 2005;Rosario et al, 2017;Zagore et al, 2018). In zebrafish dazl is expressed at all stages of GC development, but its function at this particular stage of germline development is unknown (Hashimoto et al, 2004;Howley and Ho, 2000;Kosaka et al, 2007;Maegawa et al, 1999).…”
Section: Dazl Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used the compound WIN 18,446 to inhibit retinoic acid synthesis in a fetal mouse ovary culture system that supports germ cell survival and progression through prophase I of meiosis up to diplotene arrest, followed by primordial follicle formation and subsequent growth initiation ( Stefansdottir et al . 2016 , Rosario et al 2019 ). Fetal ovaries are cultured from e13.5, a stage when germ cells are committed to oocyte development and enter the first stages of meiosis ( Adams & McLaren 2002 ); thus, in this study we are investigating the role of retinoic acid on meiotic progression, distinct from its initiation.…”
Section: Discussionmentioning
confidence: 99%